Human immunodeficiency virus type 1 DNA synthesis, integration, and efficient viral replication in growth-arrested T cells. - Li, G (1993)
Human immunodeficiency virus type 1 (HIV-1) replicates efficiently in nonproliferating monocytes and macrophages but not in resting primary T lymphocytes. To determine the contribution of cell division to the HIV-1 replicative cycle in T cells, we evaluated HIV-1 expression, integration of proviral DNA, and production of infectious progeny virus in C8166 T-lymphoid cells blocked in cell division by treatment with either mitomycin, a DNA cross-linker, or aphidicolin, a DNA polymerase alpha inhibitor. The arrest of cell division was confirmed by assay of [3H]thymidine uptake; the nondividing cells remained viable for at least 3 days after treatment. HIV-1 was expressed and replicated equally well in nondividing and dividing C8166 cells, as judged by the comparison of the levels of p24 core antigens in culture supernatants, the proportion of cells expressing HIV-1 specific antigens, the pattern and quantity of HIV-1 DNA present in the extrachromosomal and total cellular DNA fractions, and the biological activity of progeny viruses. A polymerase chain reaction-based viral DNA integration assay indicated that HIV-1 provirus was integrated in C8166 cells treated with either of the two inhibitors of cell division. Similar results were obtained by using growth-arrested Jurkat T-lymphoid cells. We conclude that cell division and cellular DNA synthesis are not required for efficient HIV-1 expression in T cells.